Implikasi Perbedaan Tafsir Building Coverage Ratio terhadap Besaran Aliran Permukaan di Suatu Kompleks Perumahan - Hadhisiswoyo, Soedarwoto (Department of Civil Engineering, Diponegoro University, 2005)
It has always been complicated to overcome an overland flow at a location with extensive percentage of land coverage condition. Regulations concerning the building coverage had decided by 60% from the area. In some certain area, it affected by land conservation that has at least 1000 m2 wide, with 10% or 20% that can be build for a real estate. The problem is not lie on the current regulations, but supervision and obedience to it seems faded. The meaning of the closing or land wide that can be build is include parking area or the coverage by semi permeable materials, and not only by the building with its’ roof. The article will discover an additional surface flow caused by a different elaboration on the regulation. The flow is affected by rainfall intensity, infiltration that is affected by soil type-this study stress on clay loam, loam, and loamy sand-the coverage material, and land elevation. Analysis is carried out on a theoretical location with building coverage ratios of 60%, 20%, and 10%. Utilizing 30 minutes rainfall intensity data and the specified return period of 5, 10, and 25 years, the additional flow dimension is obtained.Keywords: rainfall intensity, land coverage percentage, land elevation, overland flowPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3899[How to cite: Hadhisiswoyo, S., 2005, Implikasi Perbedaan Tafsir Building Coverage Ratio terhadap Besaran Aliran Permukaan di Suatu Kompleks Perumahan, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 1, pp. 80-87]